Economic burden of seasonal influenza in the United States. Issue 27 (22nd June 2018) - Putri, Wayan C.W.S.; Muscatello, David J.; Stockwell, Melissa S.; Newall, Anthony T.
Abstract: Background: Seasonal influenza is responsible for a large disease and economic burden. Despite the expanding recommendation of influenza vaccination, influenza has continued to be a major public health concern in the United States (U.S.). To evaluate influenza prevention strategies it is important that policy makers have current estimates of the economic burden of influenza. Objective: To provide an updated estimate of the average annual economic burden of seasonal influenza in the U.S. population in the presence of vaccination efforts. Methods: We evaluated estimates of age-specific influenza-attributable outcomes (ill-non medically attended, office-based outpatient visit, emergency department visits, hospitalizations and death) and associated productivity loss. Health outcome rates were applied to the 2015 U.S. population and multiplied by the relevant estimated unit costs for each outcome. We evaluated both direct healthcare costs and indirect costs (absenteeism from paid employment) reporting results from both a healthcare system and societal perspective. Results were presented in five age groups (<5 years, 5–17 years, 18–49 years, 50–64 years and ≥65 years of age). Results: The estimated average annual total economic burden of influenza to the healthcare system and society was $11.2 billion ($6.3–$25.3 billion). Direct medical costs were estimated to be $3.2 billion ($1.5–$11.7 billion) and indirect costs $8.0 billion ($4.8–$13.6 billion). These total costs were based on the estimated average numbers of (1) ill-non medically attended patients (21.6 million), (2) office-based outpatient visits (3.7 million), (3) emergency department visit (0.65 million) (4) hospitalizations (247.0 thousand), (5) deaths (36.3 thousand) and (6) days of productivity lost (20.1 million). Conclusions: This study provides an updated estimate of the total economic burden of influenza in the U.S. Although we found a lower total cost than previously estimated, our results confirm that influenza is responsible for a substantial economic burden in the U.S.